Nursing Students’ Computer Self-Efficacy and Attitudes toward Its Use in The Health Care Setting: A Comparative Study - Farida M. Hassona; Aziza Z. F. Ali; Shaimaa M. Nageeb (Evidence-Based Nursing Research)
Context: The use of technology and computers in health care has been reported to improve nurses' decision-making and competencies, which in turn increase the quality of health-care practice.